A review of the risk and precipitating factors for spontaneous coronary artery dissection - Stanojevic, Dragana; Apostolovic, Svetlana; Kostic, Tomislav; Mitov, Vladimir; Kutlesic-Kurtovic, Dusanka; Kovacevic, Mila; Stanojevic, Jelena; Milutinovic, Stefan; Beleslin, Branko (Frontiers in Cardiovascular Medicine, 2023)
Introduction Spontaneous coronary artery dissection (SCAD) accounts for 1%–4% of cases of acute coronary syndrome (ACS). SCAD is caused by separation occurring within or between any of the three tunics of the coronary artery wall. This leads to intramural hematoma and/or formation of false lumen in the artery, which leads to ischemic changes or infarction of the myocardium. The incidence of SCAD is higher in women than in men, with a ratio of approximately 9:1. It is estimated that SCAD is responsible for 35% of ACS cases in women under the age of 60. The high frequency is particularly observed during pregnancy and in the peripartum period (first week). Traditional risk factors are rare in patients with SCAD, except for hypertension. Patients diagnosed with SCAD have different combinations of risk factors compared with patients who have atherosclerotic changes in their coronary arteries. We presented the most common so-called “non-traditional” risk factors associated with SCAD patients. Risk factors and precipitating disorders which are associated with SCAD In the literature, there are few diseases frequently associated with SCAD, and they are identified as predisposing factors. The predominant cause is fibromuscular dysplasia, followed by inherited connective tissue disorders, systemic inflammatory diseases, pregnancy, use of sex hormones or steroids, use of cocaine or amphetamines, thyroid disorders, migraine, and tinnitus. In recent years, the genetic predisposition for SCAD is also recognized as a predisposing factor. The precipitating factors are also different in women (emotional stress) compared with those in men (physical stress). Women experiencing SCAD frequently describe symptoms of anxiety and depression. These conditions could increase shear stress on the arterial wall and dissection of the coronary artery wall. Despite the advancement of SCAD, we can find significant differences in the clinical presentation between women and men. Conclusion When evaluating patients with chest pain or other ACS symptoms who have a low cardiovascular risk, particularly female patients, it is important to consider the possibility of ACS due to SCAD, particularly in conditions often associated with SCAD. This will increase the recognition of SCAD and the timely treatment of affected patients.